A critical comparison of green building rating systems. (October 2017) - Doan, Dat Tien; Ghaffarianhoseini, Ali; Naismith, Nicola; Zhang, Tongrui; Ghaffarianhoseini, Amirhosein; Tookey, John
Abstract: Various green rating systems are established globally to evaluate the sustainability of construction projects. Their categories and criteria have been under constant updates to follow the sustainable trend of building development. This paper aims to develop a systematic review of the development of green rating systems. The specific objectives are: 1) discover how interest and research in green rating systems have developed; 2) identify the similarity, difference, strength and weakness of green rating systems; 3) examine whether they fully assess the projects in all aspects of sustainability. Specifically, LEED (Leadership in Energy and Environmental Design), BREEAM (Building Research Establishment Assessment Method), CASBEE (Comprehensive Assessment System for Building Environmental Efficiency) and Green Star NZ were analysed in this paper. The results indicate that BREEAM, LEED, and CASBEE have been utilized since late the 2000s while Green Star NZ is still in its earlier stages. 70% of the research papers focusing on BREEAM, LEED, CASBEE are developed geographically in the USA, Canada, the UK, China, and Australia. Although these four rating systems were initiated in different contexts with different standards, Indoor Environment Quality, Energy, and Material are core common categories for all. Environmental concerns are the main focus in New Construction manuals while Society is emphasized in Neighbourhood Development manuals. Currently, BREEAM has been the only tool which could assess all four sustainable factors. Further in-depth research is anticipated to focus more on economic and institutional factors to improve the capability of green rating systems for sustainability assessment purposes . Highlights: Indoor Environment Quality, Energy, and Material are the main focus in green rating systems. The total categories, points, and mandatory credits of analysed rating schemes tend to increase and more comprehensive. BREEAM is considered as the strongest rating system at present. Currently, no rating scheme could assess a project in all aspects of sustainability.